POLYSEGMENTAL INTERVERTEBRAL DISC HERNIATIONS OF THE LUMBAR SPINE AND THEIR SURGICAL TREATMENT (World Bulletin of Public Health, 2022)
Osteochondrosis of the spine is a disease recognized by the majority as the main cause of vertebrogenic neurological complications, polysegmental hernias in particular. According to numerous authors, the pathogenesis of the observed orthopedic and neurological complications is based on the direct and indirect mechanism of the impact of the degenerative-dystrophic process. As a radical method of treatment, medicine offers surgery. At the same time, multilevel discogenic lesions of the lumbar spine at three or more levels account for 7.03% of the total number of operated disc herniations
Keywords: Polysegmental disc herniation; pain; MRI; disability